2013
DOI: 10.1186/1746-1596-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous low-grade adenocarcinoma: an analysis of epidemiological studies and hints for pathologists

Abstract: BackgroundThis study is an analysis of the prevalence of polymorphous low grade adenocarcinoma (PLGA) in epidemiological surveys of salivary tumors published in the English language from 1992 to 2012.MethodsThese surveys included studies from different researchers, countries and continents. The 57 surveys for which it was possible to calculate the percentage of PLGAs among all malignant minor salivary gland tumors (MMSGT) were included in this review.ResultsThe statistical analyses show significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 76 publications
6
41
1
2
Order By: Relevance
“…Additionally, Woo et al [17] reported that CD43 is more strongly expressed in adenoid cystic carcinoma than PLGA, a finding that has not yet been confirmed by other investigators. Unfortunately, other immunostains, including S100 and bcl-2, have not consistently helped differentiate PLGA from either adenoid cystic carcinoma or pleomorphic adenoma [13,18,39]. p63, an immunohistochemical stain that highlights basal and myoepithelial differentiation, has never routinely been used to distinguish between PLGA, adenoid cystic carcinoma, and pleomorphic adenoma because all three lesions are frequently positive for this marker [23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Woo et al [17] reported that CD43 is more strongly expressed in adenoid cystic carcinoma than PLGA, a finding that has not yet been confirmed by other investigators. Unfortunately, other immunostains, including S100 and bcl-2, have not consistently helped differentiate PLGA from either adenoid cystic carcinoma or pleomorphic adenoma [13,18,39]. p63, an immunohistochemical stain that highlights basal and myoepithelial differentiation, has never routinely been used to distinguish between PLGA, adenoid cystic carcinoma, and pleomorphic adenoma because all three lesions are frequently positive for this marker [23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In their 2013 epidemiologic study, de Araujo et al noted a significant increase in the fraction of PLGA cases reported in the literature since 2007, but did suggest this was secondary to improved diagnostic accuracy by pathologists [16]. PLGA is most commonly found in the Caucasian population; however, some publications have reported higher incidences amongst Asian and African populations [11,16,17]. Two retrospective studies out of Northeast and Eastern China documented a lower incidence of PLGA in these regions, than that noted globally [4,18].…”
Section: Epidemiology Demographicsmentioning
confidence: 99%
“…PLGA has a female predilection, with a female-to-male ration of 2.15:1 [11,19]. PLGA is most frequent in the 6 th and 7 th decades; the age of presentation peaks during the 6 th decade [16,20]. Cases in the literature vary from the 2 nd to 10 th decades of life, with the mean age at time of diagnosis being 61.3 years of age [4,11].…”
Section: Epidemiology Demographicsmentioning
confidence: 99%
See 2 more Smart Citations